PENGARUH PENDAPATAN MASYARAKAT, KUALITAS PELAYANAN, SANKSI PERPAJAKAN, DAN NILAI JUAL OBJEK PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KOTA BANJARMASIN - Puteri, Ananda; Nordiansyah, Muhammad; Fatimah; Norlena (Jurnal Riset Akuntansi Politala, 2024)
This study aims to examine and analyze the effect of community income, service quality, tax sanctions, and selling value of tax objects on taxpayer compliance in paying Rural and Urban Land and Building Tax (PBB-P2). The population in this study is rural and urban land and building taxpayers registered with the Regional Revenue and Asset Financial Management Agency (BPKPAD) of Banjarmasin City totaling 159,175 people. The sample in the study was 100 taxpayer respondents. This study used purposive sampling method calculated by Slovin's formula. The data collection technique used in this study was a questionnaire. The type of research used is primary data from data sources obtained directly from original or first-party sources. The data analysis method was applied with multiple regression analysis using the help of IBM SPSS version 26. The results of this study show that community income, service quality, and selling value of tax objects have a significant effect on taxpayer compliance in paying PBB-P2 in Banjarmasin City. However, tax sanctions do not have a significant effect on taxpayer compliance in paying PBB-P2 in Banjarmasin City.